2014
DOI: 10.5194/hess-18-3817-2014
|View full text |Cite
|
Sign up to set email alerts
|

A physical approach on flood risk vulnerability of buildings

Abstract: Abstract. The design of efficient hydrological risk mitigation strategies and their subsequent implementation relies on a careful vulnerability analysis of the elements exposed. Recently, extensive research efforts were undertaken to develop and refine empirical relationships linking the structural vulnerability of buildings to the impact forces of the hazard processes. These empirical vulnerability functions allow estimating the expected direct losses as a result of the hazard scenario based on spatially expl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 47 publications
0
51
0
Order By: Relevance
“…Analytically and Although the indicators may give an overview of the actual situation, the links between natural process statistically sound and degree of loss, as well as the reaction of a structure to the natural process according to its characteristics, are not fully understood and, therefore, further research is required (Mazzorana et al, 2014).…”
Section: Measurementioning
confidence: 99%
“…Analytically and Although the indicators may give an overview of the actual situation, the links between natural process statistically sound and degree of loss, as well as the reaction of a structure to the natural process according to its characteristics, are not fully understood and, therefore, further research is required (Mazzorana et al, 2014).…”
Section: Measurementioning
confidence: 99%
“…Within the context of an analysis of a torrential hazard event, thereby explicitly focusing on the morphodynamic processes and not taking into account any geo-mechanical processes or the building's physics, Mazzorana et al (2014) applied the proposed concept for a residential building located at the alluvial cone of the Grossberg torrent in the Italian Alps. The study highlighted the circumstance that for medium hazard intensities, vulnerability of buildings critically depends on the patterns of water and material intrusion through openings such as doors, light shafts and windows.…”
mentioning
confidence: 99%
“…Due to the underlying empiricism of such vulnerability functions, the physics of the damage-generating mechanisms remains unveiled, and, as such, the applicability of the empirical approach for planning hazard-proof buildings is rather limited. Mazzorana et al (2014) identified the following essential requirements for vulnerability assessment of buildings exposed to fluvial hazard processes. a.…”
mentioning
confidence: 99%
See 2 more Smart Citations